Kekuatan Hukum Surat Kuasa Membebankan Hak Tanggungan (SKMHT) Sebagai Dasar Pembebanan Hak Tanggungan Dalam Perjanjian Kredit) - Ilham Dedi Perdana; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Article 15 paragraph (3) and (4) of Law No. 4 of 1996 on Mortgage has stated that, the Power of Attorney Imposing Mortgage (SKMHT) over land rights that have not been registered shall be followed by the manufacture of the Deed Granting Mortgage Not later than 3 (three) months after the given, and the Power of Attorney Imposing Mortgage (SKMHT) over land rights that has been registered shall be followed by administration of Mortgage Deed no later than 1 (one) month after awarded. The fact that happened on the field many of the parties that do not register SKMHT be APHT which the registration deadline has been set by UUHT.The purpose of this paper are: first, to determine the legal effect of SKMHT that is not registered with APHT manufacture, secondly, to determine the binding force of the Power of Attorney Imposing Mortgage (SKMHT) in credit agreements.Type of this research can be classified in this type of normative research, normative research is a law research literature. Because it makes the literature as the main focus in this research. In a normative legal research has criteria for this type of research is research that discusses the general principles of law, the data source used, primary data, secondary data, and the data tertiary data collection techniques in this study by the research literature or study documents.From the research problem there are two main things that can be inferred. First, if SKMHT not yet been registered into APHT then the debtor may extend the term of SKMHT with a record of paying with jumblah very big, because if SKMHT not be registered as APHT then SKMHT the void that would result in the creditor does not have preferential rights over object security rights if the debtor defaults or bad credit. Second, difficulties in registration SKMH are: expensive and very short period of time. Advice writer, first, Should the parties, especially creditors to consider the use of SKMHT in terms of the debtor credit borrowing, second, Should the creditor to provide credit to borrowers is not the whole at once but gradually by the time credit has been agreed.Keywords: SKMHT - APHT - Credit Agreement